Comparison of Hemoglobins from Various Subjects Living in Hypoxia - RINI PUSPITANINGRUM; KURNIA NUZTIR MANTOLINI; . RUSDI; MOHAMAD SADIKIN (Bogor Agricultural University, Indonesia, 2013)
The aim of this research was to obtain the different characteristics of haemoglobin molecules in subjects under hypoxic condition, namely eel, catfish, suckermouth fish, green sea turtle using an electrophoresis technique. We used human umbilical cord blood and thalassemia patient blood, as well as a normal adult-human blood as controls. The proteins obtained after electrophoresis process were stained with two different colouring techniques, each based on different principles. Both staining techniques gave practically identical results. Subject that live in hypoxic condition has a different haemoglobin in comparison to the one found in adult human live in normal oxygen condition (normoxia). These hypoxia-adapted or -needed hemoglobin migrate slower than adult human hemoglobin from normoxia. This observation suggests that hemoglobin which is needed to live in hypoxic condition or environment is a different molecule. Whether this hemoglobin from hypoxic condition has a higher affinity to oxygen is not yet known.